(untitled) (TAMADDUN NURI JURNALI, 2025)
This article examines the role of modern technologies in enhancing students’ intellectual knowledge. The article analyzes the integration of technologies such as digital resources, interactive learning platforms, artificial intelligence-based tools, and distance learning opportunities into the educational process. It also discusses the impact of these technologies on the development of students’ cognitive abilities, creativity, and critical thinking skills.